Performance evaluation of unit trusts in South Africa over the last two decades - Mibiola, Oluwole Jacob (My University, 2013)
Unit trust investment looks cosy and attractive from the surface, but a detailed understanding of unit trust and its performance can be daunting. Having discussed the evolution of mutual funds in the US and other industrial and financially sound countries; it is concerning that not much has been done in terms of research works on the South Africa unit trust industry’s performance. Several studies have been aimed at investigating the investment in mutual funds relative to mutual fund returns, but an extensive study on the performance of active unit trusts against their bench-marking index is still lacking. This study contributes to the debate by conducting a detailed study of the performances of mutual funds in the last two decades and also what the global investment fund witnessed over this period, with particular interest in the South African market. Another contribution of this study was to provide reasons for the slow growth of investment funds in South Africa; this study attempts to ascribe reasons as to why this has been so. This study used three different performance measures (namely: the nominal returns, Sharpe Ratios and CAPM Alphas) to test the possibility of superior performance by the market or the funds. In order to carry out this detailed analysis of the performance of unit trusts, these performance tests were applied individually to the net returns obtained from a sample of 64 South African domestic general equity unit trusts, covering the 20-year period from January 1st 1992 to December 31st 2011. This 20-year period was further divided into 7 different periods of four 5-year periods, two 10-year periods and the whole 20-year period. This was done to avoid survivorship bias. In all of the periods, strong evidence of superior performance by the domestic general equity unit trust over the market could not be found. Furthermore, several reasons were deduced form the study as to investment funds continue to experience slow growth. Some of the reasons include the following: cost of index fund, investor’s sentiments, and commissions amongst others. Finally, having said all these, outperformance, perhaps may not be the main objective of unit trusts. The findings of this study may not have provided strong evidence of outperformance, it however reveal that there is a need for unit trusts to evaluate the costs and benefits involved in their trading activities in order to provide investors with maximum possible returns for the level of risk they take.
Thesis (M.M. (Finance & Investment))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2013.
Keywords: Unit trusts; Investment; South Africa; Performance measurement